2017
DOI: 10.1098/rstb.2016.0532
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 and FKBP51: complex regulators of psychiatric diseases

Abstract: Mood disorders affect nearly a quarter of the world's population. Therefore, understanding the molecular mechanisms underlying these conditions is of great importance. FK-506 binding protein 5 () encodes the FKBP51 protein, a heat shock protein 90 kDa (Hsp90) co-chaperone, and is a risk factor for several affective disorders. FKBP51, in coordination with Hsp90, regulates glucocorticoid receptor (GR) activity via a short negative feedback loop. This signalling pathway rapidly restores homeostasis in the hypotha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 100 publications
(123 reference statements)
2
74
0
1
Order By: Relevance
“…FKBP51 levels increase with age and are additionally affected by singlenucleotide polymorphisms (SNPs) (Fujii et al 2014;Sabbagh et al 2014). FKBP51 provides a negative feedback loop: It attenuates hormone affinity in the Hsp90:GR:FKBP51 complex and GR signaling induces FKBP51 expression (Scammell et al 2001;Sanchez 2012;Criado-Marrero et al 2018). In conjunction with an environmental trigger, these factors can contribute to the onset of affective mood diseases and have further pleiotropic effects because FKBP51 competes with other cochaperones for Hsp90 binding Schulke et al 2010).…”
Section: Hsp90 and Psychiatric Diseasesmentioning
confidence: 99%
“…FKBP51 levels increase with age and are additionally affected by singlenucleotide polymorphisms (SNPs) (Fujii et al 2014;Sabbagh et al 2014). FKBP51 provides a negative feedback loop: It attenuates hormone affinity in the Hsp90:GR:FKBP51 complex and GR signaling induces FKBP51 expression (Scammell et al 2001;Sanchez 2012;Criado-Marrero et al 2018). In conjunction with an environmental trigger, these factors can contribute to the onset of affective mood diseases and have further pleiotropic effects because FKBP51 competes with other cochaperones for Hsp90 binding Schulke et al 2010).…”
Section: Hsp90 and Psychiatric Diseasesmentioning
confidence: 99%
“…Such findings can help to identify patients with an increased risk of mental disorders and to implement personalized medicine in the future. Moreover, common allelic variants in the FKBP5 gene are associated with an increased risk of developing affective disorders like anxiety, depression, and PTSD (Criado‐Marrero et al, ).…”
Section: Candidate Genes Of the Neuroendocrine Stress Response Systemmentioning
confidence: 99%
“…The stress protein FKBP51, promoted through translational research FKBP51 is a show-case of translational research where clinical and basic science approaches stimulated each other. The background of FKBP51 is laid out here only shortly, and the reader is referred to the numerous recent reviews for more detailed information [10][11][12][13][14][15]. Originally discovered as part of steroid receptor-heat shock protein 90 hetero-complexes, FKBP51 was shown to be a potent inhibitor of GR by several laboratories [16][17][18][19].…”
Section: Version Of Record Published: 22 April 2020mentioning
confidence: 99%
“…Based on these considerations, FKBP5 was included as candidate gene in an early gene association study in depression that found this gene linked to the response to antidepressant treatment [31]. Later, FKBP5 could be linked to additional stress-related diseases such as post-traumatic stress disorder [12,14]. These findings strongly amplified the interest in FKBP51 and stimulated research on its function and regulation in several laboratories; this greatly expanded the knowledge base on FKBP51's ( patho)physiological role, regulation on several levels and involvement in multiple molecular pathways, going beyond stress regulation [12,13].…”
Section: Version Of Record Published: 22 April 2020mentioning
confidence: 99%